Pharmacology of nerve growth factor and discovery of tanezumab, an anti-nerve growth factor antibody and pain therapeutic. (April 2020) - Hefti, Franz
Abstract: The pharmacology of Nerve Growth Factor (NGF) and the discovery and development of tanezumab, a monoclonal anti-NGF antibody for the treatment of pain illustrate the complex and unpredictable nature of modern drug development. Initial efforts attempted to use NGF agonistically for Alzheimer's disease and neuropathies. Most unexpectedly, clinical studies unmasked hyperalgesic effects. These observations together with new data emerging from molecular and animal model studies stimulated the idea of using an NGF antagonist for chronic pain. These events also reflect the advances of neuropharmacology from classical small molecule efforts directed at neurotransmitter receptors to modern biotechnology with significant integration in molecular biology, biochemistry, and protein engineering.